Analysis of Boiler Machine Maintenance using The Reliability-Centered Maintenance Method - Tiffany; Anita Christine Sembiring (Journal Knowledge Industrial Engineering (JKIE), 2024)
Reliability Centered Maintenance is a structured approach to identifying maintenance needs based on the function and potential failure of a system. By conducting an in-depth analysis of the function and failure of boiler engine components, this research aims to formulate the most optimal maintenance strategy. This strategy is expected to increase the overall reliability of the boiler machine and at the same time reduce the maintenance costs required. This research begins with creating a function block diagram to map the main functions and sub-functions of the boiler machine. After that, a failure mode analysis is carried out to determine its impact using the Failure Mode and Effects Analysis method) which aims to identify potential failures in each component and the consequences they cause. So it is hoped that this research can determine appropriate maintenance actions to prevent or minimize the possibility of failure. The final result of this research is structured and effective maintenance recommendations for boiler engines. These recommendations include treatment strategies tailored to previously identified functions, failure modes, and impacts. By implementing the recommendations from this research, it is hoped that the performance and service life of the boiler machine can be improved significantly.